PERTUMBUHAN POPULASI BULU BABI (Echinometra mathaei) DI PERAIRAN PESISIR KIMA BAJO KABUPATEN MINAHASA UTARA - Moningkey, Ruddy D (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
Sea urchins of different colors were collected 50 individuals each and measured their morphological characters. The data were then transformed to natural logarithm and analyzed using regression. The comparison of the regression line intercept for the shell diameter-height relationship did not show any difference, but there was a significant difference for the shell lenght-heigth relationship. The comparison between different colors exhibited variations in the shell morphology of each sea urchin population. The growth of black spined-sea urchin (Echinometra mathaei), was negative allometric; the fact that they were mostly found in the narrow crevices might have influenced their growth.